Probiotics and Prebiotics in the Aspect of Health Benefits and the Development of Novel Plant-Based Functional Food - Barbara Sionek; Aleksandra Szydłowska (Applied Sciences)
In the food market, significant changes have been observed in recent years, and what is more, they are associated with an increased “nutritional awareness” among consumers. The role of food producers is no longer limited to presenting consumers with a rich range of products; their composition is also not without significance. There is an increase in interest in the so-called “functional food”, which, in addition to traditional nutrients, also provides ingredients with specific properties that have a beneficial effect on human health. One of the types of such food is the so-called “probiotic food”. Probiotics play a key role in the design of functional foods of plant origin, as they can contribute to improving the health of the digestive system, strengthen immunity, and prophylactically act in the case of many civilization diseases. In the context of plant-based foods, particular attention is paid to the development of products that support the balance of the intestinal microbiota while providing the health benefits typical of plant-based products such as fiber, vitamins, and antioxidants. It should also be mentioned that the functional food segment in question shows not only a high trend in development in terms of the diversity of the products offered but also fits into the trend of environmentally friendly production in line with sustainable development trends. This article aimed to present the possibility of using probiotics and prebiotics in the functional innovative development of plant products. The impact of the fermentation process on the health value of the plant-derived food matrix will be discussed, as well as the technological challenges associated with this issue. This article analyzes the potential health benefits resulting from the consumption of fermented plant products and the hygiene aspects of the production process with examples of innovative probiotic plant products. It should be recognized that plant food is a promising option to deliver probiotics, paraprobiotics, and prebiotics, providing health benefits to consumers.